(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
Through this research, we have shed light on the life and work of the famous Chinese writer Li Tai Bo and the true beauty of his incomparable works. Li Bo was the most famous prominent poet of the Tang Empire, and his written monuments are endless. The poet made a great contribution to the development of literature in the Tang Empire. In the course of our research, we will consider Li Bai’s role and poems in this period.